Possible Involvement of A Monophenol Monooxygenase in A-Factor-Dependent Yellow Pigment Production in Streptomyces griseus - Jumeri Jumeri; Yasuo Ohnishi; Sueharu Horinouchi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2001)
A-factor (2-isocapryloyl-3R-hydroxymethil-γ-butyro-lactone) is an essential hormonal regulator for morphological development, as well as streptomycin and yellow pigment productions in Streptomyces griseus. By UV-treatment, three mutants that were deficient in yellow pigment production but showed normal morphologiical development and strptomycin production were obtained. A 7.5 kb-DNA fragment, which restored the yellow pigment production in one of the mutants, was shotguncloned from a chromosomal DNA of wild-type SS. griseus. Sequence analysis of this fragment showed that it contained 6 complete open reading frmaes including melC1 and melC2. MelC2 and MelC1 have high sequence similarity to monophenol monooxygenases and co-factors of the enzyme, respectively. Because a melCC2-disrupted strain showed yellow pigment deficient phenotype, it was probable that the monophenol monooxygenase homologue is involved in the biosynthesis of the yellow pigment.